Gemcitabine and oxaliplatinum: an effective regimen in patients with refractory and relapsing Hodgkin lymphoma - Gutierrez, Antonio (Onco Targets Ther, 2014)
BACKGROUND: Most Hodgkin lymphomas (HL) can be cured with current strategies. However, one-third of the cases do not respond or relapse and need salvage regimens. We report the results of a retrospective study using the gemcitabine and oxaliplatinum (GemOx) regimen. METHODS: Patients who relapsed or failed to achieve complete response were eligible and received GemOx salvage therapy. To avoid selection bias and thus to overcome the retrospective nature of the study, all treated patients were included from the pharmacy database. RESULTS: Between 2003–2013, 24 HL patients – relapsing (number [n]=12) or refractory (n=12) – were included, receiving a total of 26 induction treatments with GemOx. Mean previous regimens were 2.38 (42% relapsing after autologous transplantation). Median follow-up was 37 months, and 71% responded (38% of patients achieved complete response). The factors related to better progression-free survival were: B symptoms; response to GemOx; and consolidation with stem cell transplantation. Grades 1 and 2 neurological toxicity was present in 17% of patients. Hematological toxicity was common, with grades 3 and 4 neutropenia (25%) and thrombocytopenia (34%) observed. Progression-free survival was better in patients consolidated with stem cell transplantation. The peripheral blood stem cell collection after GemOx was successful for all candidates. CONCLUSION: 1) The GemOx regimen is effective in relapsed or refractory HL with manageable toxicity. 2) No mobilization failures were observed. 3) Consolidation after response is needed. 4) Its efficacy and favorable toxicity profile might make multiple administrations possible in several recurrences in HL.